Development of an N-Helix innovation model for the portuguese defense industry - Reis, João Carlos Gonçalves dos (2021)
This doctoral thesis in military sciences comprises a compilation of original research papers that make substantial contributions to the body of knowledge within the defense industry. These findings merit both national and international recognition, underscoring their significance through publication in scientific journals. The thesis adopts a distinctive format, presenting a cohesive compilation of three previously published empirical articles along with two supporting ones. The primary objective of this thesis is to delve into a comprehensive understanding of real-world phenomena, particularly examining the dynamics among industry, universities, and the State, as viewed through the lens of the quintuple helix innovation model (Carayannis & Campbell, 2010). Simultaneously, it aims to describe and critically assess novel and complex opportunities for the defense industry's engagement, with a focus on N-helix innovation models. Grounded in the social and military sciences, this research predominantly employs qualitative methodologies, primarily relying on case studies and various data sources such as semi-structured interviews, direct observations, and official documentation. Preliminary research findings have shown that the defense industry is gaining new momentum, as emerging technologies are enabling highly innovative and disruptive systems. This thesis addresses fundamental questions concerning the allocation of limited financial resources to foster high-tech defense industries. In this context, it is crucial to attain a nuanced understanding, analysis, and description of emerging N-helix innovation models. The core aspiration of this study is to streamline the relationship between the armed forces, the defense industry, and military universities, with a strategic focus on the efficient use and advancement of disruptive military technologies.